Motivational Interviewing: Reconciling Recovery-Focused Care and Mental Health Nursing Practice. (1st September 2020) - Mullen, Antony; Isobel, Sophie; Flanagan, Karen; Key, Kylie; Dunbar, Anna; Bell, Alison; Lewin, Terry J.
Abstract: Motivational interviewing (MI) is a long-established evidenced-based intervention aimed at guiding people to implement change. Originally developed by William Miller from the United States and Stephen Rollnick from the United Kingdom, a strong emphasis for MI is the underlying 'spirit', rather than merely the specific techniques within the model. The 'spirit' of MI consists of four key components: acceptance, partnership, evocation and compassion. These have direct overlap with concepts within the personal recovery model recognised as a critical framework in delivery of contemporary mental health services for consumers. Despite this recognition, recovery concepts have struggled to gain consistent traction, particularly within inpatient mental health units. This paper proposes that MI presents one strategy for integrating recovery-focused principles within routine mental health nursing (MHN) practice. An overview of MI and its relationship with recovery principles is discussed in the context of contemporary MHN practice. Evaluation results of a locally developed MI workshop for MHNs within a regional area of New South Wales (NSW) in Australia are presented to highlight the emerging evidence for this potential. Following the workshop, MHN participants showed key improvements in knowledge and confidence scores, as well as in understanding of key MI processes and strategies. The consolidation of these skills through training and a supervision framework is outlined.